Durability of natural hydraulic lime (NHL) based TRM composites through hot water immersion method - Gunes, M. E.; Pekmezci, B. Y.; Girgin, Z. C. (SPRINGER, 2021)
The textile reinforced mortar (TRM) composites are widely utilized for the seismic strengthening of masonry walls subjected to in-plane and out-of-plane actions. The probability of out-of-plane failure via snap-through mechanism is dominated by the flexural characteristics of relatively slender masonry wall. In this study, a rapid and early decisive procedure is proposed to direct the design of TRM composite through the bending tests combining accelerated ageing. The durability of natural hydraulic lime based TRM composites, which is unknown in the current literature, is addressed for glass, basalt and carbon textiles. The interaction between fiber mesh and matrix is discussed regarding fiber type, the influence of impregnation, flexural performance and failure modes. For total five types of fabrics, the flexural capacities are compared at ambient conditions and then through hot water ageing test (immersion at 50 degrees C during 10 days). The experimental findings indicate to the importance of the interaction between fiber and matrix about the durability and ductility of TRM composites.
Keywords: Textile reinforced mortar (TRM); Natural hydraulic lime (NHL); Bending tests; Durability; Accelerated ageing; Hot water immersion; TEXTILE REINFORCED-CONCRETE; CARBON; PERFORMANCE; FIBERS; Construction & Building Technology; Engineering; Materials Science